2005
DOI: 10.1038/modpathol.3800378
|View full text |Cite
|
Sign up to set email alerts
|

Incipient chordoma: a report of two cases of early-stage chordoma arising from benign notochordal cell tumors

Abstract: Chordomas are rare malignant bone tumors primarily involving both ends of the axial skeleton that present as destructive bone lesions with a large soft tissue mass. Chordomas were previously believed to arise from notochordal remnants. However, recent studies suggest the possibility that chordomas arise from benign notochordal cell tumors. We present two cases of coccygeal incipient chordoma that strengthen the new hypothesis. The first case was an 83-year-old man who died of prostatic adenocarcinoma. The seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 5 publications
0
52
0
7
Order By: Relevance
“…One report from 2002, do describe a chordoma observed adjacent to a benign notochordal lesion in the coccyx occurring concomitant with two BNCTs in the sacrum [1]. In 2005, a report was published describing two cases with BNCTs associated with miniature chordomas (incipient chordomas) [16]. Finally, one study (2007) identified BNCTs in 7.3% (6 of 82) of sacral/coccygeal resections performed for chordoma [11].…”
Section: Discussionmentioning
confidence: 99%
“…One report from 2002, do describe a chordoma observed adjacent to a benign notochordal lesion in the coccyx occurring concomitant with two BNCTs in the sacrum [1]. In 2005, a report was published describing two cases with BNCTs associated with miniature chordomas (incipient chordomas) [16]. Finally, one study (2007) identified BNCTs in 7.3% (6 of 82) of sacral/coccygeal resections performed for chordoma [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, this theory has recently been challenged by Yamaguchi et al who proposed that chordomas instead arise from benign notochordal cell tumors [2] . The microscopic hallmark of these tumors is the presence of characteristic large cells with numerous cytoplasmic vacuoles known as physaliphorous (Greek: droplet bearing) cells.…”
Section: Introductionmentioning
confidence: 98%
“…Both cell groups are arranged in band-like formations circumscribed by basophylic, mixoid stroma [22]. Mytoses are rare and not necessarily pathologic [28].…”
Section: Introductionmentioning
confidence: 99%
“…It accounts for approximately 3-4% of primary bone tumors and is localized along the axial skeleton [6,22,28]. This tumor develops predominantly in the sacrococcygeal (50%), spheno-occipital (35%) and cervical (15%) region and is generally regarded as a locally aggressive tumor with slow progression growth rate and metastatic incidence ranging from 5 to 40% [5,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation